Investigating the Supply Chain Problems of Imputed Economic Goods in the Modern Russian Institutional Economy - Victor Konstantinov; Ildar Valiev (International Journal of Supply Chain Management, 2018)
Abstract The research was implemented with the financial support from the Russian Foundation for Basic Research (the scientific project 18-010-00636-A). It describes the supply chain problems of "imputed economic goods" in the modern Russian institutional economy. However, this problem is also global, since the institutions that restrict business and form a common social structure are the foundation of every state. The main goal is to show our point of view on a certain set of socio-economic institutions that lead to the appearance of imputed goods, as well as to show their influence on the macroeconomic indicators of the state and enterprises. In the research we suggest raising a new scientific and practical supply chain problem related to the transformation of a number of economic concepts under the influence of various institutions, for example, economic goods to the imputed economic goods, transaction costs for compulsory expenses, etc. The growth of imputed benefits has a hidden "suffocating" effect on the economy of the enterprise and the state. In Russia and in many other countries, this process has not been investigated. The reason is not only the lack of a method for determining the signs of economy compressing due to the growth of supply chain problems of imputed goods, but also the absence of such concepts in general. Therefore, in the framework of this research, a conceptual apparatus is created to describe the hidden suffocating effects on the state's economy.